Hukum Pidana Adat dalam Sistem Hukum Pidana Indonesia: Paradigma Baru Asas Legalitas - Baihaki, Ahmad; Ghiffari, Muhammad Haikal (Kertha Patrika; Vol 46 No 1 (2024)DO - 10.24843/KP.2024.v46.i01.p03, 2024)
The position of the principle of legality in the realm of criminal law is very important, the principle of legality serves to determine whether an act can be punished or not. However, over time, the provisions of the principle of legality in the new paradigm of criminal law have been softened by accommodating laws that still apply in people's lives or customary law to determine whether someone should be punished. Then what becomes interesting to discuss in this article is the urgency of softening the principle of legality in the new paradigm of criminal law and the application of customary criminal law in the National Criminal Code. This article uses legal research by using a statutory approach, conceptual approach, and historical approach. The results of the study concluded that the softening of the principle of legality in the new paradigm of criminal law is a form of realization of protection for victims of criminal acts, the criminal acts in question are criminal acts that are not regulated by law but are contrary to the principles that still apply and develop in community life. The application of customary criminal law in the National Criminal Code will be compiled through regional regulations in accordance with the function of the regional regulation itself so that regional regulations can specifically regulate customary criminal provisions that apply in the region.